Improved operation efficiency strengthens organizational quality in higher education - Péter Levente Lakatos (Competitio)
This paper examines quality assurance as an effective tool for organizational development, reviewing the theories and history of quality management. After describing the theoretical foundations used in the USA, focusing on heavy industries, it discusses European models such as TQM, ISO and EFQM systems in more detail, then moves on to critical approaches, especially with regard to the applicability and effectiveness of quality assurance in education and higher education. The second half of this paper focuses specifically on quality assurance in higher education, in particular European standards, approaching it from the perspective of internationalisation. In this context, this paper addresses the issues of brain drain, digital campus, stakeholder involvement and student-centredness. Finally, the paper concludes that quality assurance in higher education is not only an essential but a necessary process as well, which can also be the most effective tool for organizational development.